FECAL INDICATOR BACTERIA AND AQUATIC PATHOGEN BACTERIA VIBRIOS IN NAI LAGOON, NINH THUAN - Mien, Pham Thi; Huong, Le Lan; Huong, Le Hoai; Thi, Vo Hai (Vietnam Journal of Marine Science and Technology, 2009)
Monitoring fecal pollution using fecalindicator bacteria (fecal coliform - FC) and common aquatic pathogen bacteria group of Vibrios are crucial criteria for integration coastal zone mallagement.FC and Vibrio were an alyzed following standard method. Density of FC and Vibrio varied temporally and not depend on total particulate of organic matler (with R2= 0.55 and R2 = 0.66) respectively. After 30 days ofohservatio 11, there was a sudden increase in number of Vibrio in sediments. It was significant relative to tow/particulate of organic matter. Density of Vibrio was not excess the standard limit for marine aquaculture, however, dellsity of Vibrio was high in sediments with maximum of 4.59 x 102 cfu/g. Density of FC was depended on both concentration of total particulate of organic matter and human activities in Nai lagoon.